Virus transmission by ultrasonic scaler and its prevention by antiviral agent: An in vitro study. Issue 7 (28th December 2021) - Fidler, Aleš; Steyer, Andrej; Manevski, Damjan; Gašperšič, Rok
Abstract: Background: It is well recognized that dental procedures represent a potential way of infection transmission. With the COVID‐19 pandemic, the focus of dental procedure associated transmission has rapidly changed from bacteria to viruses. The aim was to develop an experimental setup for testing the spread of viruses by ultrasonic scaler (USS) generated dental spray and evaluate its mitigation by antiviral coolants. Methods: In a virus transmission tunnel, the dental spray was generated by USS with saline coolant and suspension of Equine Arteritis Virus (EAV) delivered to the USS tip. Virus transmission by settled droplets was evaluated with adherent RK13 cell lines culture monolayer. The suspended droplets were collected by a cyclone aero‐sampler. Antiviral activity of 0.25% NaOCl and electrolyzed oxidizing water (EOW) was tested using a suspension test. Antiviral agents' transmission prevention ability was evaluated by using them as a coolant. Results: In the suspension test with 0.25% NaOCl or EOW, the TCID50/mL was below the detection limit after 5 seconds. With saline coolant, the EAV‐induced cytopathic effect on RK13 cells was found up to the distance of 45 cm, with the number of infected cells decreasing with distance. By aero‐sampler, viral particles were detected in concentration ≤4.2 TCID50/mL. With both antiviral agents used as coolants, no EAV‐associated RK‐13 cell infection was found. Conclusion: We managed to predictably demonstrate EAV spread by droplets because of USS action. More importantly, we managed to mitigate the spread by a simple substitution of the USS coolant with NaOCl or EOW.